PENGARUH MOTIVASI TERHADAP HASIL BELAJARSISWA PADA MATA PELAJARAN TIK KELAS XI DI MAN 1 BUNGO PLUS KETERAMPILAN - fauziah fauziah; Arisman Sabir Arisman; Reni Guswita Reni; Puput Wahyu Hidayat puput (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
The aim of this research is to find out how much learning motivation factors influence learning outcomes. Someone who has motivation tends to devote all his abilities to obtain optimal learning results in accordance with the expected goals. The higher the motivation that students have, the more active they will be in studying and the frequency of studying will increase, so that their learning outcomes will increase. The method used in this research is a quantitative experimental method. This method was used because this research sought to find out whether there was a causal relationship between the influence of motivation on students' interest in learning in class XI ICT subjects at MAN 1 Bungo plus skills. The population in this research is class XI MAN 1 Bungo Plus Skills students. The data analysis technique in this research is Product-moment Correlation. Based on the research results, it shows that there is no influence of motivation on student learning outcomes at MAN 1 Bungo Plus Skills. From the data obtained based on the results of hypothesis testing, it is stated that the Pearson correlation for these two variables is -.235 and the significance between these two variables is .212. while the r table is 0.05 so it can be concluded that the relationship between these two variables is negative. The results of this research are that ho is accepted and ha is rejected. Keywords: Learning Motivation, Learning Outcomes